Accounting Guide - AICPA (Wiley, 2019)
It is critical to understand the complexities of the specialized accounting and regulatory requirements needed for the broker-dealer industry. This comprehensive guide has been designed to be beneficial for a wide range of professionals within the broker-dealer industry. Updates to this edition are to conform the content to current accounting standards and regulatory requirements. The updates include: SEC Release No. 34-86073, Amendment to Single Issuer Exemption for Broker-Dealers; ASU No. 2018-09, Codification Improvements; and, SEC Release Nos. 33-10532; 34-83875; IC-33203, Disclosure Update and Simplification. In addition, this edition features a new example disclosure note for revenue from contracts with customers, which has been added to the guide's illustrative financial statements and footnote disclosures.